Association between Baltic sea diet and healthy Nordic diet index with risk of type 2 diabetes mellitus: a case–control study - Abdelgawwad El-Sehrawy, Amr Ali Mohamed; Jawad, Mahmood; Hammood, Yasir Mohammed; Ballal, Suhas; Srivastava, Manish; Sani Mohammed, Jaafaru; Arya, Renu; Kalia, Rishiv; Kadhim Ahmed, Jawad; Kareem, Muthena (Frontiers in Endocrinology, 2025)
BackgroundsRecent evidence shows the beneficial effects of Baltic Sea diet score (BSDS) and healthy Nordic diet index (HNDI) on chronic diseases; however, there is no evidence to investigate them on the risk of type 2 diabetes mellitus (T2DM). The purpose of this study was to investigate the associations between BSDS and HNDI with the risk of T2DM.MethodsThis study used a case-control design with participants aged 18 to 60 diagnosed with type 2 diabetes in the last six months (225 cases, 450 controls). The evaluation of BSDS and HNDI employed a validated 168−item semi−quantitative food frequency questionnaire (FFQ). Binary logistic regression was used to determine how OBS and T2DM are related.ResultsThe mean scores for the BSDS and HNDI were 16.00 ± 2.49 and 11.99 ± 2.61, respectively. The final model, which accounted for confounding variables, indicated that increased adherence to the HNDI is associated with a reduced likelihood of developing T2DM (OR = 0.42; 95% CI 0.18–0.98; p for trend = 0.043). Additionally, a significant association was observed between lower likelihood of T2DM and higher BSDS scores in both unadjusted (OR = 0.49, 95% CI 0.31–0.77; p for trend = 0.001) and adjusted (OR = 0.48, 95% CI 0.32–0.89; p for trend = 0.003) models.ConclusionOur research shows that following a Nordic diet significantly reduces the risk of T2DM. Commitment to this dietary pattern may also reduce related risk factors. Further longitudinal studies across diverse populations are needed to validate these findings.